Assesment Pembelajaran Dalam Kurikulum Deep Learning - Sadiq, Muh Asyhad; Alimuddin, Akhyar; N, Nursalam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Assessment is the collection of relevant information, which can be accounted for in order to make decisions both in helping teachers understand students' learning needs, providing effective feedback and improving the quality of learning. Learning and assessment are cycles where assessment provides information about learning that needs to be designed. Educational units and educators are given the freedom to develop learning, teaching tools, and assessments according to the characteristics and needs of students. While learning in the deep learning curriculum is in-depth learning. Meaningful, enjoyable learning and involving students in learning,